Hypertension affects the biocompatibility and biomineralization of MTA, High-plasticity MTA, and Biodentine® - Cosme-Silva, Leopoldo [UNESP]; Dal Fabbro, Renan [UNESP]; Gonçalves, Luanna de Oliveira [UNESP]; Prado, Alana Sant'Ana do [UNESP]; Plazza, Flávia Alfredo [UNESP]; Viola, Naiana Viana; Cintra, Luciano Tavares Angelo [UNESP]; Gomes Filho, João Eduardo [UNESP] (FapUNIFESP (SciELO), 2019)
This study evaluated the effect of hypertension on tissue response and biomineralization capacity of white Mineral Trioxide Aggregate (MTA), High-plasticity MTA (MTA HP), and Biodentine® (BDT) in rats. Polyethylene tubes filled with MTA, MTA HP, BDT, and the control group (empty tubes) were placed into the dorsal subcutaneous tissue of 32 male rats (16 normotensive (NT) and 16 hypertensive rats - 8 per group). After 7 and 30 days, the polyethylene tubes surrounded by connective tissue were removed, fixed, and embedded in histological resin. The mean number of inflammatory cells was estimated in HE-stained sections, biomineralization was quantified as area (µm2) by Kossa (VK) staining, and examination by polarized light (LP) microscopy was performed. The differences amongst the groups were analyzed statistically by the Mann-Whitney or Student's t test, according to Shapiro-Wilk test of normality (p < 0.05). The inflammatory responses to all materials were greater in hypertensive rats than in NT rats (p < 0.05). Positive VK staining in MTA and BDT were more pronounced in NT rats at 7 and 30 days (p < 0.05). Birefringent structures in LP for MTA, MTA HP, and BDT were more pronounced in NT rats at 7 days (p<0.05). In rats, hypertension was able to increase inflammatory infiltrate and decrease biomineralization of the tested materials.